U.S. online shopping: Facts, fiction, hopes and dreams. (March 2015) - Schultz, Don E.; Block, Martin P.
Abstract: Much online shopping research has been viewed from the seller׳s side, i.e., volume, timing and the like. This paper looks at online shopping/buying from the buyer׳s view. Based on 285, 000+ individual responses from an online U.S. panel, the questionnaires, gathered between 2006 and 2013, form the analytical base. Findings include an increase in online shopping volume among a declining customer base. Consumer reported details such as leading online retailers (Amazon.com), online product preferences, comparisons of online and fixed location research and buying scenarios, buying influences and the like are discussed. Managerial implications and suggestions for future research are included. Highlights: Although initially developed in the U.S. and UK, online shopping is growing more rapidly in developing markets than in the originators. U.S. online shopping appears to be increasing in sales but with a declining customer base. Online shopping varies dramatically by product category, thus generalizations using consolidated data may be misleading. Consumers use differing search and research approaches when shopping online. Retail shopper cards have a major influence on brick and mortar shoppers but are not relevant with online shoppers.